Hatching Characteristics and Growth Performance of Eggs with Different Egg Shapes - S Alasahan; AG Copur (Brazilian Journal of Poultry Science, 2016)
ABSTRACT This study was carried out to identify the effect of the egg shape index on the hatchability, performance, and carcass yield of Japanese quails (Coturnix coturnix Japonica ). Eggs were incubated in three groups, according to three different egg shape index (SI) values (Group SI-I: 70.00-73.85%, Group SI-II: 73.86-77.71% and Group SI-III: 77.72-81.57%). Unhatched eggs weight loss (HEWL) was correlated with the egg shape index groups (SI-I: 18.51%, SI-II: 13.34% and SI-III: 13.96%; p<0.01), but not with the initial unhatched egg weight (HIEW), hatched egg weight (HEW), or eggshell weight of unhatched eggs (HSW) (p>0.05). The live weight of female and male chicks hatched from SI-I, SI-II, and SI-III egg shape index groups were compared at weeks 4 (female/male: 249.12/237.77, 244.69/236.35, and 241.52/229.72 g, respectively) and 5 (female/male:304.89/272.42, 295.76/274.34, and 285.42/271.29 g, respectively), and the results showed that females were heavier than males (p<0.05; p<0.01; p<0.001, respectively).The effect of egg shape index on slaughter weight (p<0.05), left leg weight (p<0.05), liver weight (p<0.01) and liver rate (p<0.01) was significant. Females were heavier at slaughter than males in the egg shape index groups SI-I (p<0.05), SI-II (p<0.05), and SI-III (p>0.05) (female/male: 296.87/283.80, 287.95/278.00 and 283.86/278.10 g, respectively). Males presented higher carcass yield in SI-I (p>0.05), SI-II (p<0.01) and SI-III (p<0.05) (female/male: 74.40/75.92, 74.50/76.44 and 74.80/76.42%) groups than females. Egg shape index had no effect on initial egg weight (IEW), shell blunt end weight (SBW), chick weight, shank length, growth performance or carcass traits, but egg shape indexwas correlated with egg length, egg width, and hatchability of fertile eggs (p<0.05).